Pengaruh variasi suhu pengeringan dan formulasi terhadap karakteristik minuman herbal daun binahong dan daun stevia - Laksita Maharina; Sigit Prabawa; Bara Yudhistira (AGROINTEK, 2022)
Binahong leaves are a plant that contains antioxidant compounds so that can be used as herbal drinks. Stevia leaves can be used as a sweetener with antioxidant compounds that can improve the taste of herbal drinks. This study aims to determine the effect of variations in drying temperature and herbal drink formulations in physical characteristics of color, chemistry including moisture content, phenol total, and antioxidant activity, as well as sensory parameters including color, smell, taste, and overall. Besides knowing the best treatment of variations in drying temperature and herbal drink formulation. This study used a Factorial Completely Randomized Design (FCRD) with two factors, namely variations in drying temperature and formulation. The drying temperature used were 55 °C, 60 °C, and 65 °C, while the binahong leaves : stevia leaves formulation used were 87.5 % : 12.5 %; 75 % : 25 %; and 62.5 % : 37.5 %. Based on the results of this study, it was found that the physical, chemical, and sensory characteristics can be influenced by the treatment of variations in drying temperature and herbal drink formulations. The best treatment for herbal drinks with variations in drying temperature and the formulation used was drying at 55 °C with the binahong leaves : stevia leaves formulation is 62.5 % : 37.5 %. The resulting characteristics are: brightness (L*) 39.605; reddish (a*) -2.307; yellowish (b*) 12.480; moisture content 7.617 %; phenol total 62.525 mg GAE/g; antioxidant activity 94.520 %, with the appearance of a yellow-brown color; the distinctive smell; sweet taste with a bitter aftertaste; and overall the panelists’ acceptance level was rather like..